Effects of organisational justice and organisational identification on some organisational outcomes in the R&D environment of a semi-conductor company. - Sim, Steven Gek Leng. (2009)
Two separate but complementary studies were conducted to study the relationships between organizational justice, organizational identification and organizational commitment. In the first study, these relationships were examined using a survey. The results showed that organizational identification moderates the relationship between organizational justice and organizational commitment. Organizational commitment in turn has an impact on certain organizational outcomes like turnover intentions. It was found that turnover intentions reduce as organizational commitment increases.